SAT0624-HPR THE IMPACT OF PSORIATIC ARTHRITIS ON FOOT HEALTH AND INDICATION OF PODIATRY NEED IN A SECONDARY CARE SETTING. (2nd June 2020) - Field, R.; Bannon, S.; Pouliase, K.; Mukherjee, S.
Abstract : Background: Psoriatic Arthritis (PsA) is a rheumatic disease affecting 0.19% of the UK population (1). It is characterised by asymmetric oligoarticular or polyarticular peripheral arthritis or axial disease with or without associated peripheral arthritis (2). Foot manifestations of synovitis, enthesitis, dactylitis and skin and nail involvement (3) are reported. Hyslop et al. have previously reported high levels of foot involvement but low current access to foot care (4). Outcome measures that include specific PsA related foot features do exist, e.g. Leeds Enthesitis Index, Tender Dactylitis Count (5). However there is currently no measure of foot involvement and impact in PsA (6). Objectives: To identify the impact of PsA on foot health and indication of podiatry need in a secondary care outpatient setting. Methods: convenience sample was taken from a consultant rheumatologist's outpatient clinic and screened. Only those with a diagnosis of PsA were included. Sampling was conducted over a ten-week period. Screening was done using the Swindon Foot and Ankle Questionnaire (SFAQ) (7), visual Analogue Scale (VAS), clinical judgement of need for podiatric intervention and the trust's eligibility criteria for routine podiatric care. Results: The sample (n=16) was 31.3% male with a median age of 59 years (range 28-81). Conclusion: Of this patient group, 81.3% had a variety of foot care needs but these were being met in a limited number of cases (25%). Far more patients (81.3%) were eligible for care in the local trust's primary care podiatry service but were not engaging with this. 50% of the sample reported difficulty standing in the past week and 27.3% found their foot pain stopped them from going to work, indicating a clear need for foot health intervention. Recommendations: -Raise awareness of availability of podiatric care for PsA patients among patients and secondary care staff. - Ensure adequate resources are allocated to manage this cohort of patients at a service provision level. - Further research involving PsA patients referred into podiatry to assess the impact of podiatric intervention. References: [1]Ogdie A et al.(2012) Prevalence and treatment patterns of psoriatic arthritis in the UK. Rheumatology. 7;52(3):568-75. [2]Cantini F, et al.(2010) Psoriatic arthritis: a systematic review. Int J Rheum Dis.13(4):300–17. [3]Huynh D and Kavanaugh A. (2015) Psoriatic arthritis: current therapy and future approaches. Rheumatology. 54:20–8. [4]Hyslop E et al. (2010) Foot problems in psoriatic arthritis: high burden and low care provision.Ann Rheum Dis.69(5):928 [5]Assessing psoriatic arthritis in your clinic – trainer manual. 2017 https://www.psoriatic-arthritis.co.uk/assessmenttools.aspx (accessed 22-6-19) [6]Carter K et al. (2019) Linking the patient experience of foot involvement related to psoriatic arthritis to the international classification of functioning, disability and health. EULAR poster abstract THU0713-HPR [7]Waller R et al. (2012) The swindon foot and ankle questionnaire: is a picture worth a thousand words?. ISRN rheumatology. 26;2012. Disclosure of Interests: None declared